2009
DOI: 10.1107/s0108270109038542
|View full text |Cite
|
Sign up to set email alerts
|

EuI2, a low-temperature europium(II) iodide phase

Abstract: Light-yellow europium(II) diiodide, prepared by the low-temperature reaction of europium and ammonium iodide in liquid ammonia at 200 K and characterized by high-resolution X-ray powder diffraction, represents a new phase for EuI2 that adopts an orthorhombic Pnma structure with all three atoms lying on 4c positions (.m.). It is isotypic with SrI2(IV). Temperature-dependent X-ray measurements performed to investigate the thermal stability of the new phase show that it decomposes irreversibly to amorphous materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…10 In this context the proposed Sr, Bamixed ABa VIII Sr VII I 5 :Eu family are promising where the Eu 2+ are likely to remain confined at the B2 (VII) site, considering the fact that Eu in ground state of EuI 2 are seven coordinated. 42,43 While the scintillation decay times in the order of several hundred ns observed in CsBa 2 I 5 :Eu 2+ and KSr 2 I 5 :Eu 2+ are unsuitable for medical imaging techniques, the mixed cation approach mentioned here may help reduce self-absorption for faster response while resisting the formation of Eu-rich aggregates or domains. Other contributing factors such as better management of intrinsic and extrinsic defects from a materials standpoint and proper integration with a photosensor will also need to be addressed for optimum detector performance.…”
Section: Consequences Of Eu Domains and Possible Sr Ba Mixed Quatmentioning
confidence: 99%
See 2 more Smart Citations
“…10 In this context the proposed Sr, Bamixed ABa VIII Sr VII I 5 :Eu family are promising where the Eu 2+ are likely to remain confined at the B2 (VII) site, considering the fact that Eu in ground state of EuI 2 are seven coordinated. 42,43 While the scintillation decay times in the order of several hundred ns observed in CsBa 2 I 5 :Eu 2+ and KSr 2 I 5 :Eu 2+ are unsuitable for medical imaging techniques, the mixed cation approach mentioned here may help reduce self-absorption for faster response while resisting the formation of Eu-rich aggregates or domains. Other contributing factors such as better management of intrinsic and extrinsic defects from a materials standpoint and proper integration with a photosensor will also need to be addressed for optimum detector performance.…”
Section: Consequences Of Eu Domains and Possible Sr Ba Mixed Quatmentioning
confidence: 99%
“…[29][30][31][32][33][38][39][40] We also employed hybrid functional (PBE0) 40 One is orthorhombic and the other is monoclinic. 42,43 In both forms the Eu ions are seven-fold coordinated. In Table I the Eu-I bond-lengths in the orthorhombic cell are listed.…”
Section: A Structural Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The precipitated phase observed in Fig. 3 is inconsistent with the cubic Suzuki structure, and also does not match any known bulk structure of EuI 2 [36]. The moire pattern indicates that the precipitate is a 2D sheet, weakly bound to the substrate.…”
Section: Dft Calculationsmentioning
confidence: 72%
“…However, the intermediate formed inside the liquid ammonia solution remained unclear. [6] It has been reported that the solutions of Eu and Yb likely contain hexaammine complexes [M(NH 3 ) 6 ] 2+ •2e -(M = Eu, Yb). [7] From the reactions of these two metals with AgN 3 as an oxidant in liquid ammonia, we obtained octaammine complexes of Eu II 3 .…”
Section: Introductionmentioning
confidence: 99%